Green synthesis of silver@graphene oxide nanocomposite for antibacterial, cytotoxicity assessment, and hydrogen peroxide electro-sensing. (11th April 2023) - Nam, Nguyen Thanh Hoai; Dat, Nguyen Minh; Hai, Nguyen Duy; Huong, Le Minh; Tai, Le Tan; Dat, Nguyen Tien; An, Hoang; Hung, Phan Nguyen Phu; Truong, Nguyen Tan; Son, Nguyen Truong; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract : The nanocomposite of graphene oxide and silver nanoparticles with uniform particle distribution was successfully green synthesized for bioactive assessment and hydrogen peroxoide electro-sensing application. Abstract : The nanocomposite of graphene oxide and silver nanoparticles has attracted great interest from scientists. In this work, silver@graphene oxide (Ag@GO) nanocomposite was synthesized via a biological reduction route using Andrographis paniculata extract as the reducing agent. The factors affecting the material preparation, comprising AgNO3 volume, temperature, reaction time, and the amount of GO used, were investigated to select the appropriate conditions. As a result, silver nanoparticles were indicated to successfully form spherical-shaped particles with an average size of 31.93 ± 3.42 nm at 0.8 mL of the AgNO3, pH 10, and 90 °C for 30 min of the reaction time with a ratio of AgNO3  : GO = 1 : 1, corresponding to the Ag@GO-1.6 sample. Moreover, Ag@GO-1.6 showed high antibacterial activity against both Gram-negative and Gram-positive bacteria. The composite also induced notable cytotoxicity against the cancerous KB cells while barely affecting the normal HEK-293 ones. Besides, Ag@GO-1.6 showed great sensing ability for H2 O2 with a relatively low limit of detection (2.65 μL) along with a wide detection range of 0–15 μM. Therefore, those results confirmed the potential applications of bio-synthesized Ag@GO in the medical and environmental fields.